UNITEN Smart Attendance System (UniSas) Using Beacons Sensor - Azmi M.S.M.; Zabil M.H.M.; Lim K.C.; Azman R.F.R.; Adnan N.A.N.; Azman M.A.S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bluetooth; E-learning; Energy utilization; Smartphones; Android applications; Attendance systems; Beacons; Bluetooth low energies (BLE); Bluetooth low energies (BTLE); Intelligent sensors; Smart attendance; Student attendances; Students